0009 The Yorkshire Acute Internal Medicine Simulation Programme (aims). (1st November 2014) - Kasfiki, Eirini; Burns, Adam; Aslam, Imran
Abstract : A survey of training conducted by the Royal College of Physicians of UK 1 had identified that junior medical trainees were intimidated by the prospect of becoming medical registrars. Previously there were no simulation based educational programmes addressing the needs of acute medicine trainees. We have designed a comprehensive four year programme of simulation activities for acute medicine trainees and we wish to present the results of the first year's programme. Methods: The design of the programme was based on three aspects: Curriculum - Our course is mapped to the JRCPTB curriculum. Stakeholders - The three training programme directors (TPD) were approached for information on trainees' training gaps. Trainees - An e-mail survey of training needs was conducted where all the Acute Medicine trainees were sent questions related to procedural skills, technical skills and non-technical skills. A simultaneous inventory of simulation equipment and facilities was conducted and where deficiency was identified, equipment was procured. Based on training needs assessments we have created a comprehensive programme which runs as four separate days for trainees at different levels of training. Trainees in their first year have already attended a practical skills course. (Chest drain insertion, Abdominal paracentesis, Knee arthrocentesis, Electrical Cardioversion and Central Venous catheter placement), and second year trainees have attended a simulation day in challenging clinical cases. Results: The courses run so far have demonstrated increase in participants' confidence levels. Conclusion: We believe our courses meet training needs as identified by our trainee survey and fill gaps in the training where there is lack of experience due to limited exposure to these technical and non-technical skills. Faculty recruitment and sustainability are two limiting factors identified. Human factors course will run for year three trainees and year four trainees will learn Temporary cardiac pacing and Sengstaken tube insertion. Reference: The Royal College of Physicians. The medical registrar: empowering the unsung heroes of patient care. London: RCP, 2013